The Idea of Biblical Interpretation : essays in honor of James L. Kugel - Kugel, James L.; Najman, Hindy; Newman, Judith H. (Judith Hood), 1961- (Supplements to the Journal for the study of Judaism, 2004)
Biblical and literary scholars explore themes central to the work of Kugel (classical and modern Jewish and Hebrew literature, Harvard U. and Bible, Bar Ilan U., Israel), who enlarged the field of biblical studies from a narrow focus on the origins and prehistory of the biblical texts to encompass the emergence of Scripture and its role in shaping.